Patients Satisfaction with the Chronic Disease Management Program in Indonesia Using the Importance-Performance Matrix - Kusumawardana, Ramza Aurum; Sunjaya, Deni Kurniadi; Gondodiputro, Sharon; Raksanagara, Ardini Saptaningsih; Ardisasmita, Mulya Nurmansyah; Widjajakusuma, Anggraini (Althea Medical Journal, 2024)
Background: Indonesia still has a high prevalence of hypertension and diabetes mellitus. On the other hand, essential health services were disrupted during the COVID-19 pandemic. Hence, the quality of service still needs to be prioritized. The government also obliges the government-owned primary healthcare facilities (Pusat Kesehatan Masyarakat, Puskesmas) to conduct customer satisfaction surveys to evaluate service quality. This study was conducted to analyze patients’ satisfaction with the chronic disease management program (Program Pengelolaan Penyakit Kronis, Prolanis) provided by Puskesmas in Bogor City.Methods: Quantitative research with a survey approach using the CSI-29 questionnaire was conducted from October to November 2021 on 104 Prolanis participants from 6 Puskesmas in Bogor City, West Java, Indonesia. The variables were 9 dimensions of satisfaction based on the CSI-29 questionnaire. Data was transformed using the Rasch model and analyzed using the Importance-Performance Matrix (IPM).Results: Of the 104 participants, there were 78 (75%) were satisfied with the Prolanis services provided by the Puskesmas. The IPM analysis showed that the dimensions of requirements, procedures, costs, type of service products, and attitudes of health workers had low expectations and perceived performance level.Conclusions: Most of the Prolanis participants were satisfied with the Prolanis services provided by the Puskesmas in Bogor City.